Enterovirus 71 Antagonizes Antiviral Effects of Type III Interferon and Evades the Clearance of Intestinal Intraepithelial Lymphocytes - Dong, Yuanmin; Liu, Jing; Lu, Nan; Zhang, Cai (Frontiers in Microbiology, 2022)
Enterovirus 71 (EV71) is the major pathogen causing severe neurological complications and hand, foot, and mouth disease. The intestinal mucosal immune system has a complete immune response and immune regulation mechanism, consisting of densely arranged monolayer intestinal epithelial cells (IECs) and intestinal intraepithelial lymphocytes (iIELs) distributed among the IECs, which constitute the first line of intestinal mucosa against infection of foreign pathogens. As an enterovirus, EV71 is transmitted by the intestinal tract; however, the mechanisms it uses to evade the immunosurveillance of the intestinal mucosal immune system are still incompletely clarified. The present study investigated how EV71 evades from recognizing and eliminating IECs, iIELs, and iNK cells. We found that EV71 infection induced a higher level of type III interferons (IFN-λ) than type I interferons (IFN-β) in IECs, and the addition of IFN-λ markedly restricted EV71 replication in IECs. These results indicate that IFN-λ plays a more important role in anti-EV71 intestinal infection. However, EV71 infection could markedly attenuate the antiviral responses of IFN-λ. Mechanistically, 2A protease (2Apro) and 3C protease (3Cpro) of EV71 inhibited the IFN-λ production and IFN-λ receptor expression and further decreased the response of IECs to IFN-λ. In addition, we found that EV71-infected IECs were less susceptible to the lysis of intestinal NK (iNK) cells and CD3+iIELs. We revealed that the viral 2Apro and 3Cpro could significantly reduce the expression of the ligands of natural killer group 2D (NKG2D) and promote the expression of PD-L1 on IECs, rendering them to evade the recognition and killing of iNK and CD3+iIELs. These results provide novel evasion mechanisms of EV71 from intestinal mucosal innate immunity and may give new insights into antiviral therapy.